Development of Agro-edutourism Area as an Effort to Improve Welfare: Case Study of Kebun Kelulut Sangatta PT Pertamina EP Sangatta Field CSR Program - Fauziah, Elis; Pasila, Naomi Sinta; Kusuma, Oscar Mudha (Global Writing Academica Researching and Publishing, 2024)
South Sangatta Village possesses numerous potentials for development. One such potential is the presence of Trigona SP honey bee colonies that can produce honey. Honey bees are non-timber forest products with a relatively high market value. PT Pertamina EP Sangatta recognizes this as an opportunity for empowerment. In collaboration with the farmer group and Pokdarwis Trigona Reborn, PT Pertamina EP Sangatta Field, through its CRS program, seeks to develop the honey bee garden into an agro-edutourism area. This aligns with the aspirations of South Sangatta Village which aims to transform the Sangatta area into a tourism and educational hub focused on Trigona honey bees. This study aims to examine the implementation of the agro-edutourism area development program conducted by PT Pertamina EP Sangatta Field in collaboration with farmer groups and Pokdarwis Trigona Reborn. This study uses a qualitative descriptive method with a case study approach, focusing on the CSR Program of Kebun Kelulut Sangatta. Research findings indicate that the Kebun Kelulut Sangatta agro-edutourism program is a sustainable tourism initiative emphasizing local community participation. There is evidence of improved welfare, demonstrated by increased income from honey sales and tourist visits to Kebun Kelulut Sangatta. Therefore, it can be concluded that the transformation of the Kebun Kelulut into an agro-tourism site has positively impacted the economic conditions and improved the welfare of the local community.